CALD Communities as “Collateral Damage” in the Criminalization of Coercive Control: An Argument for Prioritizing Civil System Reform Over Further Criminalization in Victoria - Jones, Balawyn (Violence against women, 2025)
When posing the question of whether Victoria should follow other Australian states in criminalizing coercive control as a form of domestic and family violence (DFV), there are many arguments in favor of and against in the literature. However, scholars and advocates from marginalized communities, or in allyship with marginalized communities, tend to be cautious of embracing further criminalization, particularly due to the risks such an approach poses for women from culturally and linguistically diverse communities. This paper argues that women from marginalized communities are treated as “collateral damage” in the campaign to eliminate DFV via criminal law interventions.